Vitamin C, A and E supplementation decreases the expression of HSPA1A and HSPB1 genes in the leukocytes of young polish figure skaters during a 10-day training camp - Zychowska, M.; Jastrzebski, Z.; Chruscinski, G.; Michalowska-Sawczyn, M.; Nowak-Zaleska, A. (Journal of the International Society of Sports Nutrition, 2015)
Background: Overexpression of HSPA1A and HSPB1 has been shown to indicate stress and the degradation of damaged proteins. Therefore, the expression of these genes is often evaluated during exercise. Vitamin supplementation in young athletes may affect the expression of these genes, and help to maintain health and improve the effects of training. Methods: Fourteen top junior female athletes (age 14-15y ± 0.3 SD, body mass 51 kg ± 5 SD, and BMI of 20.15 ± 0.9 SD, time in professional training 8.5 y ± 0.5 SD) attended a conditioning camp that included meals planned by a team dietitian. To examine the effects of vitamin supplementation on antioxidant status we supplemented the athletes with either vitamin A (16 ug/kg/day), vitamin C (8 mg/kg/day) and vitamin E (1 mg/kg/day) or an inert placebo. Blood samples were taken before and after (12 h post) the camp to assess the relative expression of HSPA1A and HSPB1 mRNA in leukocytes via quantitative reverse transcription polymerase chain reaction (qRT-PCR). Results: Overall, participants trained ~135 min daily (1345 min total). No statistically significant differences in HSPA1A and HSPB1 expression were observed between the groups before the camp. In the unsupplemented group, there was a non-statistically significant increase in HSPA1A expression (100% change) and a significant increase (37% change, p < 0.05) in HSPB1 expression over the study period. The supplemented group experienced a significant decrease in HSPA1A (40% change, p = 0.01) and HSPB1 (25% change p = 0.03) expression over the study period. Conclusion: Our results indicate that supplementation with antioxidant vitamins decreases HSPA1A and HSPB1 mRNA expression in leukocytes, and thereby may reduce exercise-induced stress in young athletes, not only during training, but also in sports competitions.